PENDIDIKAN KARAKTER DALAM KONSEP PEMIKIRAN PENDIDIKAN KI HAJAR DEWANTARA - Irwansyah Suwahyu (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Character education has been an educational model offered to overcome the moral problem of children in Indonesia. This links with an increase of juvenile delinquency in society. Ki Hadjar Dewantara as one of the national education figures had contributed a lot to the progress of education in Indonesia. In this research, researcher studies about the thoughts of Ki Hadjar Dewantara about education lingking with character education. The result is the thoughts of Ki Hadjar dewantara lead to the importance of the role of the environment, the place where the character is formed, the spirit of leadership and mutual assistance, and the growth of love to the culture of the nation in order to form the successor generations of a good nation in terms of character. Keyword: Pendidikan Karakter, Pemikiran Pendidikan Ki Hadjar Dewantara, Ki Hadjar Dewantara.